Natural Killer Cells From Children With Type 1 Diabetes Have Defects in NKG2D-Dependent Function and Signaling - Qin, Huilian; Lee, I-Fang; Panagiotopoulos, Constadina; Wang, Xiaoxia; Chu, Alvina D.; Utz, Paul J.; Priatel, John J.; Tan, Rusung (Diabetes (New York, N.Y.), 2011)
Natural killer (NK) cells from NOD mice have numeric and functional abnormalities, and restoration of NK cell function prevents autoimmune diabetes in NOD mice. However, little is known about the number and function of NK cells in humans affected by type 1 diabetes. Therefore, we evaluated the phenotype and function of NK cells in a large cohort of type 1 diabetic children. Peripheral blood mononuclear blood cells were obtained from subjects whose duration of disease was between 6 months and 2 years. NK cells were characterized by flow cytometry, enzyme-linked immunosorbent spot assays, and cytotoxicity assays. Signaling through the activating NK cell receptor, NKG2D, was assessed by immunoblotting and reverse-phase phosphoprotein lysate microarray. NK cells from type 1 diabetic subjects were present at reduced cell numbers compared with age-matched, nondiabetic control subjects and had diminished responses to the cytokines interleukin (IL)-2 and IL-15. Analysis before and after IL-2 stimulation revealed that unlike NK cells from nondiabetic control subjects, NK cells from type 1 diabetic subjects failed to downregulate the NKG2D ligands, major histocompatibility complex class I-related chains A and B, upon activation. Moreover, type 1 diabetic NK cells also exhibited decreased NKG2D-dependent cytotoxicity and interferon-γ secretion. Finally, type 1 diabetic NK cells showed clear defects in NKG2D-mediated activation of the phosphoinositide 3-kinase-AKT pathway. These results are the first to demonstrate that type 1 diabetic subjects have aberrant signaling through the NKG2D receptor and suggest that NK cell dysfunction contributes to the autoimmune pathogenesis of type 1 diabetes.